4th Independent Steering Committee Meeting, 28-29 August 2018 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
In August 2018 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) held its fourth Independent Steering Committee meeting in person in Wageningen, the Netherlands.